Little Miss Muffet - Punter, Russell; Illustrated by Lorena Alvarez (London Usborne, 2012)
Little Miss Muffet is in for a surprise- a great big spider wants to join her picnic!
Include Color Illustrations
Keywords: Spiders -- Fairy Tales -- Picnics